2013
DOI: 10.3109/02652048.2013.843600
|View full text |Cite
|
Sign up to set email alerts
|

Artificial oxygen carriers based on perfluorodecalin-filled poly(n-butyl-cyanoacrylate) nanocapsules

Abstract: Poly(n-butyl-cyanoacrylate)-nanocapsules filled by perfluorodecalin (PFD) are proposed as potential oxygen carriers for blood substitute. The capsule dispersion is prepared via interfacial polymerisation from a PFD emulsion in water which in turn is generated by spontaneous phase separation. The resulting dispersion is capable of carrying approximately 10% of its own volume of gaseous oxygen, which is approximately half of the capacity of human blood. The volumes of the organic solvents and water are varied wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Transient systemic hypotension after infusion of PFC-based artificial oxygen carriers has been described long ago for PFC-based emulsion systems [ 24 , 25 ] and latterly also for capsule-based PFC-containing systems [ 26 ]. This undesirable side effect has been attributed to the action of the emulsifier without [ 27 , 28 ] or in combination with the PFC [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transient systemic hypotension after infusion of PFC-based artificial oxygen carriers has been described long ago for PFC-based emulsion systems [ 24 , 25 ] and latterly also for capsule-based PFC-containing systems [ 26 ]. This undesirable side effect has been attributed to the action of the emulsifier without [ 27 , 28 ] or in combination with the PFC [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other alternatives to pulmonary oxygenation have been explored over the past years. Perfluorocarbon-based O 2 carriers have been tested using several routes of administration, including intravenous [ 21 ], transintestinal [ 22 ], and transpleural [ 23 ], as well as for liquid ventilation [ 24 ]. Nevertheless, none of these agents has been approved for clinical use due to storage, production, and clinical evaluation complications [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative option to guarantee a stable formulation without Ostwald ripening and the disadvantage of prolonged excretion time is the encapsulation of PFC with polymers, for example poly(lactide-co-glycolide) (Ferenz et al 2013, 2014) or poly( n -butyl-cyanoacrylate) (Stephan et al 2014; Laudien et al 2015). Potential areas of application for nanocapsules with a polymer-based shell are controlled drug delivery (Singh and Nalwa 2011; Byagari et al 2014; Huang et al 2013; Jiang et al 2013) and artificial oxygen carriers (Stephan et al 2014; Laudien et al 2015; Xiong et al 2013). The thin capsule wall provides compatibility with the aqueous medium blood and allows easy release or absorption of respiratory gases (Stephan et al 2014).…”
Section: Main Textmentioning
confidence: 99%
“…Potential areas of application for nanocapsules with a polymer-based shell are controlled drug delivery (Singh and Nalwa 2011; Byagari et al 2014; Huang et al 2013; Jiang et al 2013) and artificial oxygen carriers (Stephan et al 2014; Laudien et al 2015; Xiong et al 2013). The thin capsule wall provides compatibility with the aqueous medium blood and allows easy release or absorption of respiratory gases (Stephan et al 2014). Our recent toxicity studies showed insufficient biocompatibility of poly( n -butyl-cyanoacrylate) (Laudien et al 2015) (see “Reasons for failure of PFC-based preparations in clinical trials”).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation